You are on page 1of 9

# Transverse vibration of a cantilever beam The dierential equation of motion that describe the transverse vibration of a beam is given

as 2y 4y m 2 + EI 4 = f (x, t) t x (1)

where y, m, E, and I are the transverse deection, mass per unit length, Young modulus of elasticity, and second moment of area of the cross-section of the beam, and f (x, t) is the loading per unit length of the beam. Free vibration of the beam: In the case of free vibration, f (x, t) = 0, and the equation reduces to 2y 4y + a2 4 = 0 t2 x where a2 = EI . m (2)

(3)

Using the method of separation of variables, we assume a solution of the form y(x, t) = (x)q(t) (4)

where (x) is a function which depends only on space, and q(t) only on time. Substituting Eq. (4) into Eq. (2), and simplifying, we obtain a2 1 d4 1 d2 q = = 2 dx4 q dt2 (5)

where is a constant to be determined. Equation (5) can be rewritten as d4 4 = 0 dx4 and d2 q + 2q = 0 dt2 4 = m 2 2 = . a2 EI (6)

(7)

where

(8)

The general solutions of Eqs. (6) and (7) are given as (x) = c1 sin(x) + c2 cos(x) + c3 sinh(x) + c4 cosh(x) and q(t) = c5 sin(t) + c6 cos(t) Free vibration of a cantilever beam: The above solutions apply to free transverse vibration of any beam. In this section, we will derive the solution specically for a cantilever beam shown in Fig. 1. For this beam, the boundary conditions are 1. The displacement and the slope of the beam at the xed end are zero, and 2. The moment and the shear force on the beam at the free end are zero. These conditions can be written in mathematical form as y(0, t) = y 2y 3y (0, t) = (L, t) = (L, t) = 0 x x2 x3 (11) (10) (9)

where L is the length of the beam. Equation (11) implies that (0, t) = d d2 d3 (0, t) = 2 (L, t) = 3 (L, t) = 0 dx dx dx (12)

Dierentiating Eq. (9) three times with respect to x, we obtain d = (c1 cos(x) c2 sin(x) + c3 cosh(x) + c4 sinh(x)), dx d2 = 2 (c1 sin(x) c2 cos(x) + c3 sinh(x) + c4 cosh(x)), 2 dx and d3 = 3 (c1 cos(x) + c2 sin(x) + c3 cosh(x) + c4 sinh(x)). 3 dx (13) (14)

(15)

Substituting Eq. (12) into Eqs. (9), (13), (14) and (15), we obtain c2 + c4 = 0, c1 + c3 = 0, c1 sin(L) c2 cos(L) c1 sinh(L) c2 cosh(x)) = 0, 2 (16) (17) (18)

Piezoceramics

a x0
Figure 1. Cantilever Beam

and c1 cos(L) + c2 sin(L) c1 cosh(L) c2 sinh(L) = 0. Equations (18) and (19) can be written in matrix form as a11 a12 a21 a22 where a11 , a12 , a21 , and a22 are given as a11 = sin(L) + sinh(L), a12 = cos(L) + cosh(L)), a21 = cos(L) + cosh(L), a22 = sin(L) + sinh(L). (21) (22) (23) (24) c1 c2 = 0 0 (20) (19)

For nontrivial solution, the determinant of the matrix in Eq. (19) must be 0. This leads to cos(L) cosh(L) + 1 = 0. (25)

This is a nonlinear equation which has innite roots, the rst 4 roots of which are given as L = 1.8751, 4.6941, 7.8548, 10.9955. (26)

For a rectangular beam, we have I = bh3 /12 and m = bh, where b and h are the width and the thickness of the beam, and is the density of the beam material. Using Eq. (8) and the expressions for I and m, we get 2 = 4 or EI Ebh3 Eh2 = 4 = 4 m 12bh 12

E (L)2 h E 2 = = h 12 12 L2 Using Eqs. (26) and (27), the rst 4 frequencies of the beam are given as = 1.0150 h L2 h E , 6.3608 2 L h E , 17.8105 2 L h E , 34.9014 2 L E .

(27)

(28)

Since L has innite values, also has innite values. In other words, the system has innite frequencies. This is because the system is continuous, and all continuous systems have innite number of frequencies. 3

Using Eq. (18), the ratio of c2 upon c1 can be written as sin(L) + sinh(L) c2 = c1 cos(L) + cosh(L)) (29)

Substituting c1 = c3 and c4 = c2 (see Eqs. 16 and 17) into Eq. (9), we get (x) = c1 (sin(x) sinh(x) + c2 (cos(x) cosh(x)) c1 (30)

where c2 /c1 is given by Eq. (29). Note that for dierent values of , we get dierent (x)s, known as the mode shapes, and dierent q(t)s, known as the generalized coordinates . Properties of the mode shapes: Let us represent dierent mode shapes as j (x), j = 1, , . Note that these mode shapes satisfy Eq. (6). Thus, we have d4 j (x) 4 = j j (x) dx4 Multiplying both sides by k (x) and integrating from 0 to L, we get
L 0 4 j j (x)k (x)dx = L 0

(31)

L 0

L 0

L

(32)
0

## Using the boundary conditions (Eq. (12)), Eq. (31) reduces to

L 0 4 j j (x)k (x)dx = L 0

(33)

## Switching the role of j (x) and k (x), we obtain

L 0 4 k k (x)j (x)dx = L 0

(34)

L 0

j (x)k (x)dx = 0

(35)

and
L 0

(36)

0

(j (x))2 dx = 1,

(37)

## then from Eq. (33), it follows that

L 0

d2 j (x) dx2

2 4 dx = j

(38)

Equation (35) is known as the orthogonality condition. In other words, the mode shapes j (x), j = 1, , are orthogonal. The mode shapes are also called the eigenfunctions. When Eq. (37) is satised, the mode shapes (eigenfunctions) are called the normal mode shapes (normalized eigenfunctions), and Eq. (35) is called the orthonormality condition. Forced vibration: Let us now consider force vibration of the cantilever beam. For this case, 2y 4y 1 + a2 4 = f (x, t) 2 t x m (39)

## Using the method of separation of variables, the displacement y can be written as

y(x, t) =
j=1

j (x)qj (t)

(40)

where j (x) are the normal mode shapes determined above. Substituting this into Eq. (39), we obtain
4 j (x) 1 2 qj 2 j (x) 2 + a qj (t) = f (x, t) 4 t x m j=1 j=1

(41)

Multiplying Eq. (41) both sides by k (x) and integrating from 0 to L, we obtain (after some simplication) 1 2 qj 2 + j qj (t) = 2 t m
L 0

## j (x)f (x, t),

j = 1, ,

(42)

Note that for a given value of j, Eq. (42) represents force vibration of a single degree-of-freedom spring-mass system. Since j varies from 1 to , a cantilever beam can be thought of as a system consisting of innite single degree-of-freedom springmass system. Consequently, the response of a vibrating cantilever beam may have innite frequency. Further, force f (x, t) would cause all generalized coordinates qj (t), 5

j = 1, , to change with the following exception. If the initial conditions of a generalized coordinate are zero and the associated mode shape leads the right hand side of Eq. (42) to be zero, then this generalized coordinate would not be excited. To get a better understanding of the system and the response of the system, assume that initially the beam is in rest position and f (x, t) is a point force acting at a point x0 . In this case, the initial conditions and the force f (x, t) can be written as y(x, 0) = and f (x, t) = (x x0 )f (t) (44) y(x, 0) =0 t (43)

where (x x0 ) is the delta function. Since, Eq. (43) must be satised at all points of the beam, we obtain, using Eqs. (40) and (43) that qj (0) = qj (0) = 0 Substituting Eq. (44) into Eq. (42), yields 2 qj 1 2 + j qj (t) = j (x0 )f (t), t2 m j = 1, , (46) (45)

Note that if for certain j = J, J (x0 ) = 0, then qJ (t) = 0, i.e. qJ (t) will not be excited. Let us now consider that the force is an impulsive force. In this case, force f (t) can be written as f (t) = F0 (t), and Eq. (46) reduces to 2 qj 1 2 + j qj (t) = j (x0 )F0 (t), 2 t m j = 1, , . (47)

Here, F0 is the amplitude of the force. Integrating Eq. (47) from 0 to 0+ , we obtain
0+ 0

2 qj dt + t2

0+ 0

2 j qj (t)dt

0+ 0

j = 1, , ,

1 j (x0 )F0 , m

j = 1, , ,

(48)

0+ 0

qj (t)dt = 0, 6

(49)

0+ 0

(t)dt = 1,

(50)

## and q(0 ) = 0. (51)

Equation (49) follows because qj (t) is continuous, Eq. (50) is a property of the delta function, and Eq. (51) is the second part of Eq. (45). For t > 0, Eq. (47) is given as 2 qj 2 + j qj (t) = 0 t2 The solution of this equation is given as qj (t) = Aj sin(j t) + Bj cos(j t) Since, qj (0) = 0 and qj (0+ ) = j (x0 )F0 /m, it follows that Aj = j (x0 )F0 , mj and Bj = 0 (54) (53) (52)

Using Eqs. (53) and (54), we obtain qj (t) = j (x0 )F0 sin(j t) mj

(55)

Substituting Eq. (55) into Eq. (40), we obtain the Vertical displacement as y(x, t) = F0 m j (x)
j=1

j (x0 ) sin(j t) j

(56)

Note that the contribution of a mode to the overall signal depends on the location where the load is applied, the frequency of the mode, and the point where the signal is measured. Measurement of vibration using a piezoceramic: Modeling of a piezoceramic is dicult. This is because piezoceramic patches have nite dimension, and the strain over that patch may vary. For simplicity, we will assume that the strain over the piezoceramic is uniform, and it is equal to the strain at the center of the patch. Further, many other factors such as bonding eect, Poisson eect, error in orientation, etc. are neglected. With these in mind, the strain at the piezoceramic patch can be given as = h d2 y(a, t) F0 h d2 j (x) j (x0 ) h1 = = |x=a sin(j t) 2 2 2 rc 2 dx 2m j=1 dx j 7 (57)

where rc is the radius of curvature of the centerline of the beam, and a is the location of the center of the patch. Since, the voltage generated in the piezoceramic patch is proportional to the strain in the patch, the voltage is given as V =k = kF0 h d2 j (x) j (x0 ) |x=a sin(j t) 2 m j=1 dx j (58)

where k is a proportionality constant. Here, a factor 2 has been applied with the assumption that we have two piezoceramic patches in series such that the voltage add.